New Insights into the Symbiotic Relationship between Orchids and Fungi - Yeh, Chuan-Ming; Chung, KwiMi; Liang, Chieh-Kai; Tsai, Wen-Chieh (Applied sciences, 2019)
Mycorrhizas play an important role in plant growth and development. In mycorrhizal symbioses, fungi supply soil mineral nutrients, such as nitrogen and phosphorus, to their host plants in exchange for carbon resources. Plants gain as much as 80% of mineral nutrient requirements from mycorrhizal fungi, which form associations with the roots of over 90% of all plant species. Orchid seeds lack endosperms and contain very limited storage reserves. Therefore, the symbiosis with mycorrhizal fungi that form endomycorrhizas is essential for orchid seed germination and protocorm development under natural conditions. The rapid advancement of next-generation sequencing contributes to identifying the orchid and fungal genes involved in the orchid mycorrhizal symbiosis and unraveling the molecular mechanisms regulating the symbiosis. We aim to update and summarize the current understanding of the mechanisms on orchid-fungus symbiosis, and the main focus will be on the nutrient exchange between orchids and their fungal partners.